BARGAINING MANAGEMENT STRATEGY, ACCOUNTING FOR LOVE AND LANGUAGE IN THE FRAME OF PHILOSOPHY IBNU SINA - Arif Widyatama; Tjiptohadi Sawarjuwono (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2026)
This article aims to examine and reconstruct the concept of Small and Medium Enterprises (SMEs) bargaining strategy as a source of relational competitive advantage, especially when compared to the strategic approach of large companies that tend to be impersonal. This study proposes that MSMEs' bargaining strategy is not merely an economic mechanism, but also a social and moral practice that can strengthen long-term relationships between sellers and buyers. By integrating the concepts of love, accounting language, and transaction ethics, this article uses the philosophical framework of Ibn Sina which is based on two main principles, namely Divine Light and Existence. Through a conceptual-philosophical approach, this study shows that the implementation of a bargaining strategy based on Ibn Sina's philosophy requires three main prerequisites: (1) the intention of MSMEs that is rooted in divine values, (2) the use of contextual and adaptive economic communication language towards transaction partners, and (3) the morality of business actors in conveying values ​​and prices honestly to build emotional bonds based on mutual trust. This article contributes to the literature on accounting and MSME strategy by offering an alternative perspective based on Islamic philosophy that places love, ethics, and human relations as the foundation of economic practice.